MOTIVASI BELAJAR MATEMATIKA SISWA PADA PROJECT BASED LEARNING DENGAN PENDEKATAN TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE - Muawanah; Romadhona, Reny; Cipta, Dyah Ayu Sulistyaning (Universitas Insan Budi Utomo, 2024)
The aim of this research is to increase students' learning motivation which is eroded by the presence of gadgets. The low motivation to learn mathematics is the background for the research conducted by researchers in class VII of Sukodono Islamic Middle School. To respond to this, the researchers conducted classroom action research which aims to increase students' learning motivation so that can increase the achievement of learning objectives in accordance with the implementation of the curriculum in schools. Students' learning motivation will emerge if they are directly involved in the learning process, one of the innovative learning models that involves students is the PjBL model. The steps in the PjBL model require students to think critically, creatively and innovatively in solving problems given by educators. Apart from using learning models that involve students, using interesting learning media can increase learning motivation. One application that can be used as a learning medium that increases student motivation is the Canva application. Therefore, researchers used the PjBL model with Canva media in research which is expected to increase the motivation of class VII students at Sukodono Islamic Middle School in PLSV material. The results of this research show that 2 students or 8.7% of the 23 students have not met the criteria for achieving learning objectives. The author concludes that the PjBL model is recommended to be applied to mathematics learning.